Target Selection and Evaluation Practices in Innovation-Driven Big Tech M&As: Case Studies from Google and IBM - Isic, Nevena (2024)
This research investigated the target selection and evaluation practices of Big Tech companies for M&A in the context of acquiring innovation. Using Eisenhardt’s case study method, the case studies of Google's acquisition of Motorola and IBM's acquisition of Red Hat were analyzed and compared through two key perspectives– overall corporate and specific strategic perspective. The study combined primary data collected through semi-structured interviews with M&A specialists from Google and IBM and publicly available secondary data.